PENGARUH PERPUTARAN PIUTANG DAN PERSEDIAAN TERHADAP MODAL KERJA PADA KOPERASI SEJAHTERA BERSAMA PAGAR AGUNG KOTA LAHAT - Sahila Sahila (Jurnal RATRI (Riset Akuntansi Tridinanti), 2020)
The purpose of this study was to determine how much influence the accounts receivable and inventory turnover have on working capital at the Sejahtera Bersama Pagar Agung cooperative, Lahat. Secondary data is used for research in the form of financial statements which are sampled by purposive sampling, namely the period 2017 to 2019.The result of the research is that Accounts Receivable Turnover and Inventory Turnover simultaneously have a significant effect on working capital, the value of f count 112,480>F table of 3.28, with a significant less than 0.05, which is 0.000. Accounts receivable turnover has a significant effect on working capital with t count 4.849> t table 2.03457 with a significant less than 0.05 and Inventory Turnover has a significant effect on working capital with a value t count 3.673> t table value 2.03457 with a significant less than 0, 05. Keywords: Accounts Receivable Turnover, Inventory Turnover, Working Capital